Tumor-induced double positive T cells display distinct lineage commitment mechanisms and functions - Schad, Sara E; Chow, Andrew; Mangarin, Levi; Pan, Heng; Zhang, Jiajia; Ceglia, Nicholas; Caushi, Justina X; Malandro, Nicole; Zappasodi, Roberta; Gigoux, Mathieu; Hirschhorn, Daniel; Budhu, Sadna; et al. (The Journal of experimental medicine, 2022)
Transcription factors ThPOK and Runx3 regulate the differentiation of "helper" CD4+ and "cytotoxic" CD8+ T cell lineages respectively, inducing single positive (SP) T cells that enter the periphery with the expression of either the CD4 or CD8 co-receptor. Despite the expectation that these cell fates are mutually exclusive and that mature CD4+CD8+ double positive (DP) T cells are present in healthy individuals and augmented in the context of disease, yet their molecular features and pathophysiologic role are disputed. Here, we show DP T cells in murine and human tumors as a heterogenous population originating from SP T cells which re-express the opposite co-receptor and acquire features of the opposite cell type's phenotype and function following TCR stimulation. We identified distinct clonally expanded DP T cells in human melanoma and lung cancer by scRNA sequencing and demonstrated their tumor reactivity in cytotoxicity assays. Our findings indicate that antigen stimulation induces SP T cells to differentiate into DP T cell subsets gaining in polyfunctional characteristics.